Movie Success Prediction System Using Python and Machine Learning Algorithms - Singh, Mohit (International journal for research in applied science and engineering technology, 2025)
In the entertainment industry, predicting the success of a movie is a crucial task. With advancements in technology, machine learning has emerged as a powerful tool for predicting the success of movies. In this research paper, we aim to develop a machine learning-based movie success prediction system using Python. To achieve this goal, we will collect and preprocess movie data from various sources. The data preprocessing stage will involve cleaning and selecting relevant features that contribute to the prediction of movie success. This paper will also explore the key features to consider when developing a machine learning-based movie success prediction system. Through this research, we hope to provide insights into the effectiveness of machine learning algorithms in predicting movie success.